Assessing the Capability of Chemical Ameliorants to Reduce the Bioavailability of Heavy Metals in Bulk Fly Ash Contaminated Soil - Joy Kumar Mandal (MDPI AG, 2021)
In-situ rehabilitation of fly ash at dumping sites has rarely been addressed for crop production due to growth-related constraints, largely of heavy metal (HM) contamination in soils and crops. Current communication deals with a novel approach to identify a suitable management option for rejuvenating the contaminated soils. In this background, a 60-days incubation experiment was conducted with different fly ash-soil mixtures (50 + 50%, A1; 75 + 25%, A2; 100 + 0%, A3) along with four ameliorants, namely, lime (T1), sodium sulphide (T2), di-ammonium phosphate (T3), and humic acid (T4) at 30 ± 2 °C to assess the ability of different fly ash-soil-ameliorant mixtures in reducing bio-availability of HMs. Diethylenetriaminepentaacetic acid (DTPA)-extractable bio-available HM contents for lead (Pb), cadmium (Cd), nickel (Ni), and chromium (Cr) and their respective ratios to total HM contents under the influence of different treatments were estimated at 0, 15, 30, 45, and 60 days of incubation. Further, the eco-toxicological impact of different treatments on soil microbial properties was studied after 60 days of experimentation. A1T1 significantly recorded the lowest bio-availability of HMs (~49–233% lower) followed by A2T1 (~35–133%) among the treatments. The principal component analysis also confirmed the superiority of A1T1 and A2T1 in this regard. Further, A1T1 achieved low contamination factor and ecological risk with substantial microbial biomass carbon load and dehydrogenase activity. Thus, liming to fly ash-soil mixture at 50:50 may be considered as the best management option for ameliorating metal toxicity. This technology may guide thermal power plants to provide the necessary package of practices for the stakeholders to revive their contaminated lands for better environmental sustainability.